2002
DOI: 10.3168/jds.s0022-0302(02)74355-5
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genetic Correlations of Test Day Milk Yield and Composition, Individual Laboratory Cheese Yield, and Somatic Cell Count for Dairy Ewes

Abstract: Genetic parameters for milk yield, contents of fat, total protein, casein and serum protein, individual laboratory cheese yield, and somatic cell counts (SCC) were estimated from 7492 monthly test-day records of 1119 Churra ewes. Estimates were from multivariate REML using analytical gradients (AG-REML) procedures. Except for fat content, estimates for the other routinely recorded traits (milk yield, protein content, and SCC) agreed with those previously obtained in this and other dairy sheep populations. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
54
9
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 37 publications
34
54
9
4
Order By: Relevance
“…Heritability estimates, based on repeatability test-day models, range from 0.04 to 0.16 for several breeds including the Churra (Baro et al, 1994;El-Saied et al, 1998;Othmane et al, 2002), the Manchega (Serrano et al, 2003), the East Friesian (Hamann et al, 2004) and the Valle del Belice sheep breeds (Riggio et al, 2007). Other studies reported similar or slightly higher heritability estimates (from 0.11 to 0.18) for the average SCS during lactation, for Chios (Mavrogenis et al, 1999), Lacaune (Barillet et al, 2001;Rupp et al, 2003a), Latxa (Legarra and Ugarte, 2005) and Manech Red Faced ewes (Barillet et al, 2008).…”
Section: Genetic Parameters Of Scc and Mastitis In Sheepmentioning
confidence: 99%
“…Heritability estimates, based on repeatability test-day models, range from 0.04 to 0.16 for several breeds including the Churra (Baro et al, 1994;El-Saied et al, 1998;Othmane et al, 2002), the Manchega (Serrano et al, 2003), the East Friesian (Hamann et al, 2004) and the Valle del Belice sheep breeds (Riggio et al, 2007). Other studies reported similar or slightly higher heritability estimates (from 0.11 to 0.18) for the average SCS during lactation, for Chios (Mavrogenis et al, 1999), Lacaune (Barillet et al, 2001;Rupp et al, 2003a), Latxa (Legarra and Ugarte, 2005) and Manech Red Faced ewes (Barillet et al, 2008).…”
Section: Genetic Parameters Of Scc and Mastitis In Sheepmentioning
confidence: 99%
“…On a lactation basis, moderate heritabilities for milk yield have been reported in Lacaune (0.30; Barillet, 1997) and Sarda (0.30;Sanna et al, 1997), whereas the estimates are slightly lower in Spanish breeds such as Manchega (0.18;Serrano et al, 1996), Latxa (0.21; Legarra & Ugarte, 2001) and Churra (0.26; Othmane et al, 2002). Protein and fat yield heritabilities range from 0.16-0.18 (Latxa; Legarra & Ugarte, 2001) to 0.32-0.35 (Manech).…”
Section: Current Selection Objectivesmentioning
confidence: 99%
“…The models of Serrano et al (2001) and Othmane et al (2002) were identical in their application to our data. The coefficients of determination of the validated models ranged from 0.7600 (P-LDIM) to 0.7999 (P-FLTY).…”
Section: Fixed Effectsmentioning
confidence: 99%
“…Relationships between the milk production and the fecundity traits (litter size, number of weaned lambs) should be further analyzed by including a multi-trait approach. The milk-component effects could be used to optimize BV for milk product yield, as the dry matter content and the milk yield are negatively correlated (Othmane et al, 2002;Komprej et al, 2009), and product yield depends on both the parameters. When more records are available and the data have better connectedness, which can be facilitated by broader production recording, the random regression of days-in-milk should be tested as well.…”
Section: Potential Models For a Further Developmentmentioning
confidence: 99%
See 1 more Smart Citation